College physics with an integrated approach to forces and kinematics. Volume 2 - Giambattista, Alan; Ricardson, Betty McCarthy; Richardson, Robert C. (Robert Coleman) 1949- (New York McGraw-Hill Higher Education, 2010)
Mechanics; Thermal physics; Electromagnetism; Electromagnetic waves and optics; Quantum and particle physics and relativity
Part 3, Part 4, part 5 Includes index.
Keywords: Physics -- Textbooks; Vật lý; Vật lí